2018
DOI: 10.1371/journal.pone.0200728
|View full text |Cite
|
Sign up to set email alerts
|

Reduced microbiome alpha diversity in young patients with ADHD

Abstract: ADHD is a psychiatric disorder which is characterized by hyperactivity, impulsivity and attention problems. Due to recent findings of microbial involvement in other psychiatric disorders like autism and depression, a role of the gut microbiota in ADHD pathogenesis is assumed but has not yet been investigated. In this study, the gut microbiota of 14 male ADHD patients (mean age: 11.9 yrs.) and 17 male controls (mean age: 13.1 yrs.) was examined via next generation sequencing of 16S rDNA and analyzed for diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
242
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(264 citation statements)
references
References 99 publications
18
242
0
4
Order By: Relevance
“…No clear overall conclusion could be drawn from the studies. The two studies originating from Europe observed that the gut microbiota β-diversity of ADHD cases differed from controls, 65,66 whereas none of the two East-Asian studies observed any significant differences. , Furthermore, changes in individual bacteria were inconsistent between the four studies.…”
Section: Studies Investigating Gut Microbiota In Adhd Cases Yield Incmentioning
confidence: 92%
See 3 more Smart Citations
“…No clear overall conclusion could be drawn from the studies. The two studies originating from Europe observed that the gut microbiota β-diversity of ADHD cases differed from controls, 65,66 whereas none of the two East-Asian studies observed any significant differences. , Furthermore, changes in individual bacteria were inconsistent between the four studies.…”
Section: Studies Investigating Gut Microbiota In Adhd Cases Yield Incmentioning
confidence: 92%
“…Only three studies used gender-matched cases and controls. 52,54,66 We also recorded information regarding the use of special diets or nutritional supplements, presence of GI symptoms as well as the use of medication. We found that for three studies investigating ASD 45,58,59 and one study investigating ADHD, the diet, or use of probiotics, of cases differed from that of controls.…”
Section: Characteristics Of Studies Investigating Asd or Adhdmentioning
confidence: 99%
See 2 more Smart Citations
“…As researchers uncover more details regarding which gut commensals may play a significant role in host health, a promising application for this knowledge is towards developing a stool-based test to evaluate the health status tied to one's own gut microbiome. Among several measures of gut ecological properties, Shannon diversity in particular has frequently been applied for comparing gut microbiomes implicated in health and disease [16][17][18] . So far, however, there is no conclusive evidence that such gross characteristics are a reliable and accurate measure to explain variations in health traits 19,20 .…”
Section: Introductionmentioning
confidence: 99%